Dampak Media Digital dalam Meningkatkan Kemampuan Bahasa Indonesia di SDN 10 Tiumang Kabupaten Dharmasraya - Khoirunnisaa, Aziizah; Aldani, Vigo; Alwi, Nur Azmi; Syam, Salmaini Safitri (Fakultas Sastra Universitas Muslim Indonesia, 2025)
This study aims to investigate how students at SDN 10 Tiumang can improve their Indonesian language skills through the use of digital media. The research employed a qualitative method with data collected through documentation, interviews, and observations. The findings indicate that the integration of digital media in Indonesian language learning enhances students’ enthusiasm and develops language skills in speaking, listening, reading, and writing. Moreover, the increase in students’ learning motivation was found to be significantly correlated with the use of digital media. The integration of such media provides concrete contributions to language skill development, including speaking through digital presentations and online discussions, listening through audio-visual materials, reading through interactive digital texts, and writing through word-processing applications and text-sharing platforms. These findings are supported by previous studies that highlight the great potential of digital media in driving innovation in Indonesian language education. The implications of this study emphasize the importance of well-planned and integrated digital-based learning strategies to optimize Indonesian language mastery at the elementary school level. By utilizing digital media effectively, students are expected to build a strong language foundation that not only supports their future studies but also prepares them to face communication challenges in the digital era.